Why link diverse citizen science surveys? Widespread arboreal habits of a terrestrial amphibian revealed by mammalian tree surveys in Britain - Petrovan, Silviu O.; Al-Fulaij, Nida; Christie, Alec; Andrews, Henry (PLOS ONE, 2022)
Terrestrial anurans, with their typically short limbs, heavy-set bodies and absent claws or toe pads are incongruous tree climbers, but even occasional arboreal locomotion could offer substantial advantages for evading predators or accessing new shelter or food resources. Despite recent interest, arboreal behaviour remains rarely and unsystematically described for terrestrial amphibians in Europe, likely due to fundamental differences in survey methods and therefore a lack of field data. However, other taxa surveys specifically target trees and tree cavities. We undertook collaborations and large-scale data searches with two major citizen science projects surveying for arboreal mammals in Britain to investigate potential tree climbing by amphibians at a national scale. Remarkably, we found widespread arboreal usage by amphibians in England and Wales, with occupancy of hazel dormouse (Muscardinus avellenarius) nest boxes, tree cavities investigated as potential bat roosts and even a bird nest, by common toads (Bufo bufo), but few additional records of frogs or newts. Of the 277–400 sites surveyed annually for dormice since 2009 at least 18 sites had amphibians recorded in nest boxes while of the 1388 trees surveyed for bats a total 1.4% (19 trees) had toads present. Common toads were found using cavities in seven tree species and especially goat willow (Salix caprea). Toads are potentially attracted to tree cavities and arboreal nests because they provide safe and damp microenvironments which can support an abundance of invertebrate prey but the importance of such tree microhabitats for toad conservation remains unknown and our results should be interpreted cautiously. We encourage expanding and linking of unrelated biodiversity monitoring surveys and citizen science initiatives as valuable tools for investigating ecological traits and interactions.